Gestión sostenible de los desechos peligrosos en los establecimientos de lubricación de vehículos del cantón caluma, provincia de bolívar - Arias Morales, Jenny Margoth (2024)
Ecuador has a large number of vehicles and car wash and lubrication centers, which generate serious environmental problems due to the inadequate management of hazardous waste generated by their economic activity; therefore, the objective of this research is to plan the sustainable management of hazardous waste in vehicle lubrication establishments in the Caluma canton. For which a research with holistic approach and non-experimental design was developed, where the following types of research were applied: diagnostic, field and descriptive; likewise, observation, deductive and analytical methods were used, which, supported by the use of the interview, direct observation and Leopold Matrix, relevant information on the subject was obtained. The results of the investigation reveal that hazardous waste, wastewater and burned oils are not adequately treated; oil filters are dumped in the municipal landfill or delivered without any economic value. In addition, only one establishment contracted with a certified manager, while the grease traps and washing machine buckets are not adequately maintained. The environmental impact assessment found that only two facilities generated the most environmental contamination, with a score of -22 and -25, indicating low adversity, where the biotic factor (aquatic flora and fauna) is the most affected, and the operating processes that generate the most contamination were engine and chassis washing and cleaning of the work area. For this reason, the most relevant measures considered in the sustainable management plan consist of training lubricator employees on good environmental practices, regulatory bases, and general recommendations on hazardous waste management.